Implementasi Aplikasi Duolingo dalam Meningkatkan Kosa Kata Bahasa Inggris - Nur Aisyah; M. Hasan Hidayatullah (Bidayatuna, 2023)
Since English is a subject that all students in Indonesian schools are required to study, schools are under pressure to make studying the language enjoyable for the pupils. The use of the Duolingo app to increase the English vocabulary of Grade 3 A MI Tarbiyatul Islam pupils is discussed in this study. memorizing a language involves memorizing a lot of vocabulary. This study employs a qualitative case study methodology. Four people the head of the madrasa, an English teacher, and two Class 3 A students from MI Tarbiyatul Islam served as the study's informants. Data gathering, data reduction, data display, and conclusions are all used in data analysis. According to the research findings, the Duolingo application can increase students' vocabulary acquisition because of its supporting elements, which include an initial ability analysis, engaging the students' attention, repetition, and practice questions.